How Students Solves PISA Tasks: An Overview of Students’ Mathematical Literacy - Hendroanto, Aan; Istiandaru, Afit; Syakrina, Nisa; Setyawan, Fariz; Prahmana, Rully Charitas Indra; Hidayat, Agus Sofian Eka (Universitas Ahmad Dahlan, 2018)
This article aims to investigate how mathematics education students in Universitas Ahmad Dahlan solve PISA mathematics problems. This research used the descriptive method with the qualitative approach and supported with quantitative data. Research subjects were 20 new students of mathematics education at Universitas Ahmad Dahlan in the 2016/2017 academic year. We translated the 2012 PISA instrument and used it to collect data on students’ mathematical literacy skills and to identify their difficulties. All the data were analyzed based on PISA’s framework. The result shows that, in general, 65.7% of students were able to understand the problems and plan their strategies to solve them. Meanwhile, only 46.9% among them could answer correctly. In addition, only 36.8% of the students were able to understand the level 6 problems while only 23.7% among them answered correctly. The students performed well in the interpretation process towards the problems with individual and social contexts. However, they found difficulties in the formulation and employment process of the problems, especially in the work and scientific context.